Analisis Konsep Pemeliharaan Jalan Terkait Keterbatasan Alokasi Anggaran Di Wilayah Sumbagsel - Desi Meriana (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
Inter Urban Road Management (IRMS) is an integrated software system used to help roadplanners to take data and to plan national and province road maintenance programs. The exampleof IRMS output producing strategies in maintenace handling was in the East Cross of Lampungprovince in Pematang Panggang segment – Sp. Pematang had AADT value of 7,601, AC-WCsurface type, Link Program 2008 of BW(betterment widening), Link Program 2009 of R (routinemaintenance), Link Program 2012 of R (routine maintenance). Handling in 2008 was bettermentwidening from International Roughness Index (IRI) 8.6 into 3.4 (improved road condition) andeconomically the produced investment calculation was NPV/C 154,060,000 (positive). Thecorellation of budget allocation, AADT and road condition was by giving priorities of budgetprograms according to necessity so that the road condition, in this case IRI, would improve andthe AADT value would increase or vice versa. Less budget allocation for road handling causedless proper road conditions. AADT decreased with an assumption that traffic movement wouldchoose better alternative roads.